Cicadidae types (Hemiptera-Cicadomorpha) housed at the Museo de La Plata entomological collection (Argentina) - de Remes Lenicov, Ana M. Marino; Maciá, Arnaldo; Pianzola, Bruno (Zootaxa, 2015)
A catalog of the 161 type specimens of species of Hemiptera Cicadidae housed in the collection of the Entomology Division of the Museo de La Plata is presented. This collection represents 52 species grouped in 19 genera. For each species the original and current names, bibliographic references, type category, number of specimens, gender, Museo de La Plata code numbers, and transcription of data from labels (country, province, locality, date of collection, collector’s name, and hosts) are given. Information about the state of preservation of the specimens in each series and photographs of each type species are also provided.